Shopping festival atmospherics of China’s singles day shopping festival and participants’ perception: Scale development and validation - Jingyu Li; Xiaoming Wang; Qiuyang Gu (PLoS ONE, 2025)
China’s Singles Day Shopping Festivals (SDSFs) have continuously attracted consumers in recent years. As large-scale online sales events, their atmospherics have not yet been systematically analyzed. The present study aims to develop a measurement scale named “shopping festival atmospherics” (SFA) to capture the major dimensions of the atmospherics created by SDSFs. Following a rigorous procedure, both qualitative and quantitative approaches are employed to develop the measurement scale. Finally, three dimensions (cultural cues, social cues, and online cues) that contain eighteen attributes are extracted. The present study also identifies several novel shopping atmospheric cues that have not been mentioned in the literature. The happily crowded environment (“Renao” in the Chinese language) is a positive atmospheric cue for Chinese participants. A fair shopping environment is also a positive atmospherics cue as participants worry about price scams. Finally, the limitations and suggestions for future research are presented at the end of the paper.